Space, people and technology Reclaiming the narrative on cities - Osman, Amira (The Built Environment in Emerging Economies (BEinEE): Cities, Space and Transformation, 2023)
In this book, there is a call on built environment professionals to reflect on the role of narrative in shaping space, influencing people and making decisions about technology. It is argued that by changing the narrative and methods of representations, new imaginaries can be generated and the scope of what is possible is significantly broadened. Contextualized narratives, vocabularies and metaphors can evoke new thinking and new practice. This book looks for examples where professionals and communities have jointly worked together from the precinct to the site level. The authors are especially inspired by the ideas of 'tinkering', 'muddling through', 'engaging with the mess' and 'gnarly planning', concepts that encourage experimentation and engagement with real-life contexts, learning through doing, policy change through evolutionary processes and a hands-on approach. This book aims to elevate our understanding of the concepts of people-centred participation and co-production/co-creation by shifting the debate from the esoteric to the applied and contextual. We believe that practice can only be transformed by transforming thinking. Through the development of our own philosophies, emerging from and rooted in context, we may shift thinking and practice towards people, community and care.